Acellular Dermal Matrix Reduces Myofibroblast Presence in the Breast Capsule. Issue 5 (May 2019) - Tevlin, Ruth; Borrelli, Mimi R.; Irizarry, Dre; Nguyen, Dung; Wan, Derrick C.; Momeni, Arash
Abstract : Background: Capsular contracture remains a common complication after implant-based breast reconstruction. Previous work has suggested that the use of acellular dermal matrix (ADM) reduces the rate of capsular contracture, though little is understood about the underlying mechanism. As myofibroblasts are believed to be the key cells implicated in contracture formation, we hypothesized that ADM would result in a reduction in periprosthetic myofibroblast concentration. Methods: Five patients who underwent immediate prepectoral tissue expander placement with anterior ADM coverage and an inferior cuff were included. At the second stage, tissue samples were obtained of both ADM and capsule from each reconstructed breast. Samples were then prepared for hematoxylin and eosin staining and immunohistochemistry for myofibroblast identification (alpha smooth muscle actin and vimentin positive and desmin negative) and analysis. Experimental values are presented as mean ± SD unless otherwise stated. Statistical significance was determined using unpaired t test. Results: Successful incorporation of ADM was noted in all cases. A significant reduction in myofibroblast concentration was noted in the ADM versus the capsule ( P = 0.0018). This was paralleled by significantly thicker periprosthetic capsule formation overlying the formerly raw pectoralis major muscle, that is, not covered by ADM ( P < 0.0001). Conclusions: In the presence of ADM, there are significantly fewer myofibroblasts in breast capsules and thinner capsules on histology. Given the central role of myofibroblasts in the development of clinically significant capsular contracture, this study unmasks a possible mechanism for the protective effect of ADM with respect to capsular contracture development.